Application of Artificial Intelligence in Improving Customer Experience at PT Chubb Life Insurance Medan (Jurnal Manajemen Bisnis, 2024)
This research discusses the application of Artificial Intelligence in improving Customer Experience at PT Chubb Life Insurance Medan. Artificial Intelligence plays an important role in increasing customer loyalty and customer relationships. Artificial intelligence is a symbol of the emergence of the industrial revolution 4.0 era which is intended to provide convenience for users, in various sectors, especially in the insurance sector. With Artificial Intelligence, customers can easily connect with each other without having to be on location, or formulate an event or condition. The approach used in this research is qualitative, which is intended to understand the phenomena experienced by the research subject. This research produces data in the form of descriptive words and written words about people and observed behavior. The results of this study indicate that the application of Customer Corner in improving Customer Experience has a positive impact. Various service features in the Customer Corner web are online customer services that make it easy for customers to get policy information, partner hospitals, and claim forms. How to check the balance of Chubb Life insurance or the amount of the annual limit can also be seen in the Chubb Life online customer portal.